Cellulose-based environment-friendly plastic substitute material and preparation method thereof

By combining the nanofiller of the molybdenum disulfide nanosheet composite transition metal carbide with the lignin-containing nanocellulose suspension, and adding polyvinyl alcohol under the action of citric acid cross-linking to form a dense composite material, the problem of insufficient heat resistance and hydrophobicity of the cellulose material is solved, and the service life of the material is significantly improved.

CN119708641AActive Publication Date: 2025-03-28NINGBO JINYI ELECTRONIC TECHNOLOGY CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411960530.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Due to the existence of molecular structure and strong hydrogen bond network, cellulose materials are prone to moisture and deterioration and heat deformation, resulting in poor heat resistance and hydrophobicity, which limits their service life.

Method used

The nanofiller using molybdenum disulfide nanosheets composite transition metal carbide is combined with the lignin-containing nanocellulose suspension, and through the cross-linking of citric acid and the addition of polyvinyl alcohol, a dense composite material is formed to enhance the mechanical properties, hydrophobicity and heat resistance of the material.

Benefits of technology

It significantly enhances the toughness, hydrophobicity and heat resistance of the composite material, reduces fracture and deformation caused by moisture or heat, and extends the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119708641A_ABST
    Figure CN119708641A_ABST
Patent Text Reader

Abstract

The invention discloses a cellulose-based environment-friendly plastic substitute material and a preparation method thereof, and relates to the technical field of high polymer materials. The cellulose-based environment-friendly plastic substitute material is prepared from a molybdenum disulfide nanosheet composite transition metal carbide nanofiller, a lignin-containing nanocellulose suspension, citric acid, glycerol and polyvinyl alcohol, the molybdenum disulfide nanosheet composite transition metal carbide nanofiller is composed of molybdenum disulfide nanosheets and transition metal carbides. Nanofiller of molybdenum disulfide nanosheets compounded with transition metal carbides is dispersed in lignin-containing nanocellulose suspension, and gaps in a lignin-containing nanocellulose structure are fully filled under the crosslinking action of citric acid, so that a stable and compact network structure is formed; the toughness, hydrophobicity and heat resistance of the composite material are remarkably enhanced, and the problems of fracture, deformation and the like caused by dampness or heating are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of polymer materials, and specifically refers to an environmentally friendly plastic substitute material based on cellulose and a preparation method thereof. Background Art

[0002] Plastics have been widely used in the packaging field due to their low cost, ease of use, chemical resistance, easy processing, high transparency, high strength and other advantages. However, a large amount of plastic waste leaks into the soil, water and other natural environments, and is difficult to degrade, causing visual pollution, soil damage, microplastics and other environmental hazards. In the plastic recycling process, due to poor management systems, high costs, and low recycling rates, only a very small amount of plastic waste is ultimately recycled, and the rest of the unrecycled plastic waste eventually accumulates in landfills or enters the natural environment. Therefore, while non-degradable petroleum-based plastics bring convenience to human society, they also pose a serious threat to global organisms and the environment.

[0003] The development of green and degradable packaging materials using renewable resources is of great significance for solving the environmental problems caused by petroleum-based plastics. As the most abundant natural renewable polymer material on earth, cellulose has become an important raw material for the sustainable development of human society due to its low cost, sustainability, good biocompatibility and excellent biodegradability. It is considered to be the main driving force of the future energy and chemical industries.

[0004] The existing technology currently has the following problems:

[0005] Due to its molecular structure and strong hydrogen bond network, cellulose is easily affected by moisture, which reduces the quality of the material. It is also easily deformed by high temperature. Its poor heat resistance and hydrophobicity limit the service life of cellulose-based materials. Summary of the invention

[0006] In view of the above situation, in order to overcome the defects of the prior art, the present invention proposes an environmentally friendly plastic substitute material based on cellulose, comprising the following components in parts by weight: 20-30 parts of nanofiller of molybdenum disulfide nanosheet composite transition metal carbide, 40-50 parts of lignin-containing nanocellulose suspension, 2-4 parts of citric acid, 3-5 parts of propylene glycol, and 10-15 parts of polyvinyl alcohol.

[0007] The molybdenum disulfide nanosheet composite transition metal carbide nanofiller comprises the following components in parts by weight: 30-40 parts of molybdenum disulfide nanosheets and 10-20 parts of transition metal carbide.

[0008] The lignin-containing nanocellulose suspension is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate, and combining the pretreatment with a high-pressure homogenization mechanical treatment.

[0009] The method for preparing the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps:

[0010] (1) Disperse 30-40 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid in 25 mL of ultrapure water, perform ultrasonic treatment for 5-6 hours, centrifuge at 3000-4000 rpm for 10 minutes, take the supernatant and centrifuge at 7000-8000 rpm for 10 minutes, collect the product, and separate thinner molybdenum disulfide sheets from the blocky molybdenum dioxide by chemical stripping. The thinner sheets can be used as plasticizers for filler modification, improve the brittle fracture of cellulose materials, and have good mechanical properties. In addition, the sulfur atoms in the surface structure of molybdenum disulfide present certain protrusions, thereby achieving hydrophobic properties, which can reduce the occurrence of water absorption and moisture problems of cellulose materials, and obtain molybdenum disulfide nanosheets;

[0011] (2) Add 0.8-1.0g lithium fluoride to 20mL hydrochloric acid solution with a mass fraction of 30%, then slowly add titanium aluminum carbide under gentle stirring, and then stir at 30-35°C for 12-24h. Wash the resulting mixture with water until the pH is 6.0, then ultrasonicate for 0.5-1h, centrifuge at a speed of 2000-3000rpm for 20-30min, and vacuum dry the precipitate to obtain a transition metal carbide, which has a multilayer structure and a large surface area, improves the barrier properties, and reduces the entry of moisture. The nanometer size and good mechanical properties of this two-dimensional material can also enhance the strength and toughness of the cellulose material. The stable structure of the transition metal carbide can also enhance the heat resistance of the cellulose material, so that it can still maintain stable performance at high temperatures;

[0012] (3) Dispersing the molybdenum disulfide nanosheets described in step (1) in 5-10 mL of water, stirring for 10-20 min, and then adding the transition metal carbide described in step (2) thereto, ultrasonically treating for 15-20 min, and then centrifuging. The precipitate is dried, and thinner and smaller molybdenum disulfide nanosheets are attached to the multiple layers of transition metal carbide to form a special layered structure, which effectively fills the gaps between the cellulose matrix and exhibits excellent mechanical properties, hydrophobic properties and heat resistance. It can reduce the deformation and fracture of cellulose materials caused by moisture and heat. The carrier effect of the transition metal carbide also reduces the accumulation and agglomeration of the molybdenum disulfide nanosheets, thereby obtaining a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides;

[0013] Preferably, in step (2), the amount of titanium aluminum carbide added is 0.8-1.0 g. Titanium aluminum carbide has a hexagonal layered structure, and the aluminum atomic layer in titanium aluminum carbide can be etched by lithium fluoride and hydrochloric acid to prepare a new type of multi-layer two-dimensional material.

[0014] The present invention also provides a method for preparing an environmentally friendly plastic substitute material based on cellulose, which specifically comprises the following steps:

[0015] S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate were mixed at a molar ratio of 1:1, stirred in an oil bath at 70-80°C for 3-4h, cooled at room temperature, and then the obtained low eutectic solvent was heated to 110-120°C, followed by adding 9.0-10.0g wheat straw, and stirring was continued for 3-4h. After the reaction was completed, the wheat straw treated with the low eutectic solvent was filtered and washed with deionized water, the filter residue was vacuum dried and dispersed in 50mL water, mechanically treated with a high-pressure homogenizer, and circulated at a pressure of 120-130MPa. After 8-10 treatments, more holes appeared on the surface of the wheat straw residue after the low eutectic solvent pretreatment, and the original smooth and complete structure was severely damaged. Hemicellulose and part of lignin were removed. Combined with high-pressure homogenization mechanical treatment, the obtained wheat straw residue was smaller in size and more thermally stable. The preparation method of lignin-containing nanocellulose using wheat straw as raw material can also be realized. The remaining lignin can be used as a natural binder to enhance the bonding between components, further enhance the mechanical properties, make it not easy to break, and obtain a lignin-containing nanocellulose suspension.

[0016] S2, disperse the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50mL deionized water, stir for 20-30min, then add citric acid, continue stirring for 20-30min, and then mix with the lignin-containing nanocellulose suspension described in step S1, and magnetically stir for 1-2h. The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide is evenly and stably dispersed on the structure of lignin-containing nanocellulose, effectively filling the gaps therein, forming a dense network structure, which can be used as a stress concentration point, can transmit and disperse external force, enhance mechanical properties, reduce fracture, and can also highly isolate the entry of moisture, reducing the risk of moisture. The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide contains C, O, N, and S elements. These doped elements can enhance the stability of the material crystal, thereby significantly improving the heat resistance and obtaining a dense composite material;

[0017] S3, adding polyvinyl alcohol to 50mL of deionized water, heating and stirring at 70-80°C for 2-3h, cooling at room temperature, and then mixing evenly with the dense composite material described in step S2, stirring for 30min, and finally adding propylene glycol, magnetically stirring for 1h, standing to defoam, and then cross-linking at 120-130°C for 10-15min, transferring to a plastic culture dish, drying to form a film at room temperature for 48h, and drying and storing after removing the film. The addition of polyvinyl alcohol further improves the heat resistance of the dense composite material and can also increase its transparency, so that it still has a certain aesthetic value as a plastic substitute material. The material prepared by this process has good toughness, hydrophobicity and heat resistance, and significantly extends the service life of the material, thereby obtaining an environmentally friendly plastic substitute material based on cellulose;

[0018] Preferably, in step S2, the amount of citric acid added is 0.2-0.4 g, and citric acid can form intermolecular covalent diester bonds with the transition metal carbide and the hydroxyl groups of the lignin-containing nanocellulose, thereby cross-linking and stabilizing the structure, thereby improving the dispersion and bonding force between the nanofiller of the molybdenum disulfide nanosheet composite transition metal carbide and the matrix, and preventing the nanosheet filler from falling off;

[0019] Preferably, in step S3, the amount of glycerol added is 0.3-0.5 g. An appropriate amount of glycerol as a plasticizer can make the material have better toughness and extend the service life.

[0020] The beneficial effects achieved by the present invention are as follows:

[0021] The present invention disperses nanofillers of molybdenum disulfide nanosheets and composite transition metal carbides in a suspension of lignin-containing nanocellulose, and forms a dense composite material under the cross-linking action of citric acid, which fully fills the gaps in the structure of lignin-containing nanocellulose to form a stable and dense network structure, significantly enhancing the toughness, hydrophobicity and heat resistance of the composite material, reducing problems such as breakage and deformation caused by moisture or heat, and then further synthesizing an environmentally friendly plastic substitute material based on cellulose with polyvinyl alcohol and glycerol, effectively improving the performance of the material and extending its use period. The molybdenum disulfide nanosheet composite transition metal carbide nanofiller has a molybdenum disulfide nanosheet attached to multiple sheets of transition metal carbide to form a special layered structure. The carrier effect of the transition metal carbide reduces the accumulation and agglomeration of the molybdenum disulfide nanosheet. The attachment of the molybdenum disulfide nanosheet increases the stability and complexity of the layered structure, effectively reduces the entry of moisture, enhances heat resistance, and can also play the role of a plasticizer, which can improve the strength and toughness of the cellulose material, present excellent mechanical properties, hydrophobic properties and heat resistance, and reduce the damage of the cellulose material caused by moisture and heat. The invention solves the problems of fracture, deformation and the like; in the dense composite material, the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide is evenly and stably dispersed in the structure containing lignin nanocellulose under the action of citric acid, fully filling the missing gaps and forming a dense network structure, which can enhance toughness, reduce fracture, and highly isolate the entry of water, reduce moisture absorption, and the C, O, N, S elements doped in the nanofiller can enhance the stability of the material crystal, thereby improving the heat resistance. Among them, citric acid can not only enhance the compatibility and dispersion stability of the nanofiller and the matrix, but also enhance the compatibility and dispersion stability of the nanofiller and the matrix. The molybdenum disulfide nanosheets can also be cross-linked with the residual lignin in the matrix, further enhancing the binding force and dispersion compatibility, and the cross-linking effect of citric acid can also reduce the hydrophilicity of the hydroxyl group, which is beneficial to reducing the moisture phenomenon caused by water absorption; the present invention uses molybdenum disulfide nanosheets composite transition metal carbide nanofillers, lignin-containing nanocellulose suspension, citric acid, propylene glycol and polyvinyl alcohol to prepare an environmentally friendly plastic substitute material based on cellulose, which has excellent mechanical properties, hydrophobic properties and heat resistance, reduces fracture and deformation caused by moisture and heat, and significantly extends the service life of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the dense composite material prepared in Example 1 of the present invention;

[0023] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0024] Figure 3The water vapor transmission rate results of Examples 1-4 and Comparative Examples 1-3 of the present invention are shown in FIG.

[0025] Figure 4 This is a graph showing the decrease rate of elongation at break of Examples 1-4 of the present invention and Comparative Examples 1-3. DETAILED DESCRIPTION

[0026] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0027] Unless otherwise defined, all professional and scientific terms used herein have the same meanings as those familiar to those skilled in the art. In addition, any methods and materials similar or equivalent to those described herein may be applied to the present invention. The preferred implementation methods and materials described herein are for demonstration purposes only and are not intended to limit the content of this application.

[0028] The experimental methods in the following examples are conventional methods unless otherwise specified; the experimental materials used in the following examples are purchased from commercial channels unless otherwise specified.

[0029] Example 1

[0030] This embodiment proposes an environmentally friendly plastic substitute material based on cellulose, comprising the following components in parts by weight: 30 parts of nanofiller of molybdenum disulfide nanosheets composite transition metal carbide, 50 parts of lignin-containing nanocellulose suspension, 4 parts of citric acid, 5 parts of glycerol, and 15 parts of polyvinyl alcohol.

[0031] The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide comprises the following components in parts by weight: 40 parts of molybdenum disulfide nanosheet and 20 parts of transition metal carbide.

[0032] The lignin-containing nanocellulose suspension is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate and combining it with a high-pressure homogenization mechanical treatment.

[0033] The preparation method of the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps:

[0034] (1) 40 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid were dispersed in 25 mL of ultrapure water, ultrasonically treated for 6 h, and then centrifuged at 4000 rpm for 10 min. The supernatant was centrifuged at 8000 rpm for 10 min, and the product was collected. Thinner molybdenum disulfide sheets were separated from the bulk molybdenum dioxide by chemical stripping. The thinner sheets can be used as plasticizers for filler modification, improve the brittle fracture of cellulose materials, and have good mechanical properties. In addition, the sulfur atoms in the surface structure of molybdenum disulfide present certain protrusions, thereby achieving hydrophobic properties, which can reduce the occurrence of water absorption and moisture problems of cellulose materials, and obtain molybdenum disulfide nanosheets;

[0035] (2) 1.0 g of lithium fluoride was added to 20 mL of a 30% hydrochloric acid solution, and then titanium aluminum carbide was slowly added under gentle stirring. The amount of titanium aluminum carbide added was 1.0 g. Titanium aluminum carbide has a hexagonal layered structure. The aluminum atomic layer in titanium aluminum carbide can be etched by lithium fluoride and hydrochloric acid to prepare a new type of multilayer two-dimensional material. The mixture was then stirred at 35°C for 24 hours. The resulting mixture was washed with water until the pH was 6.0, and then ultrasonicated for 1 hour, centrifuged at a speed of 3000 rpm for 30 minutes, and the precipitate was vacuum dried to obtain a transition metal carbide. It has a multilayer structure and a large surface area, which improves the barrier properties and reduces the entry of water. The nanometer size and good mechanical properties of this two-dimensional material can also enhance the strength and toughness of cellulose materials. The stable structure of the transition metal carbide can also enhance the heat resistance of cellulose materials, so that it can still maintain stable performance at high temperatures;

[0036] (3) The molybdenum disulfide nanosheets described in step (1) are dispersed in 10 mL of water and stirred for 20 min. The transition metal carbide described in step (2) is then added thereto. The mixture is ultrasonically treated for 20 min and then centrifuged. The precipitate is dried. The thinner and smaller molybdenum disulfide nanosheets are attached to the multiple layers of transition metal carbide to form a special layered structure, which effectively fills the gaps between the cellulose matrix and exhibits excellent mechanical properties, hydrophobic properties and heat resistance. The deformation and fracture of the cellulose material caused by moisture and heat can be reduced. The carrier effect of the transition metal carbide also reduces the accumulation and agglomeration of the molybdenum disulfide nanosheets, thereby obtaining a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides.

[0037] This embodiment provides a method for preparing an environmentally friendly plastic substitute material based on cellulose, which specifically comprises the following steps:

[0038] S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate were mixed at a molar ratio of 1:1, stirred in an oil bath at 80°C for 4h, cooled at room temperature, and then the obtained low eutectic solvent was heated to 120°C, followed by adding 10.0g wheat straw and stirring for 4h. After the reaction was completed, the wheat straw treated with the low eutectic solvent was filtered and washed with deionized water, and the filter residue was vacuum dried and dispersed in 50mL water, and mechanically treated with a high-pressure homogenizer. The treatment was circulated for 10 times at a pressure of 130MPa. More holes appeared on the surface of the wheat straw residue after pretreatment with the low eutectic solvent, and the original smooth and complete structure was severely damaged. Hemicellulose and part of the lignin were removed. Combined with the high-pressure homogenization mechanical treatment, the obtained wheat straw residue was smaller in size and more thermally stable. The preparation method of lignin-containing nanocellulose using wheat straw as raw material can also be realized, wherein the remaining lignin can be used as a natural binder to enhance the bonding between components, further enhance the mechanical properties, make it not easy to break, and obtain a lignin-containing nanocellulose suspension;

[0039] S2, disperse the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50mL deionized water, stir for 30min, then add citric acid, continue stirring for 30min, the amount of citric acid added is 0.4g, citric acid can form intermolecular covalent diester bonds with the hydroxyl groups of transition metal carbide and lignin-containing nanocellulose, so as to crosslink and stabilize the structure, improve the dispersion and bonding force between the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide and the matrix, prevent the nanosheet filler from falling off, and then mix with the lignin-containing nanocellulose suspension described in step S1, magnetic After 2 hours of vigorous stirring, the nanofillers of the molybdenum disulfide nanosheet composite transition metal carbide are evenly and stably dispersed on the structure of the lignin nanocellulose, effectively filling the gaps therein and forming a dense network structure, which can be used as a stress concentration point, can transmit and disperse external forces, enhance mechanical properties, reduce fractures, and can also highly isolate the entry of moisture and reduce the risk of moisture. Among them, the nanofillers of the molybdenum disulfide nanosheet composite transition metal carbide contain C, O, N, and S elements. These doped elements can enhance the stability of the material crystal, thereby significantly improving the heat resistance and obtaining a dense composite material;

[0040] S3, adding polyvinyl alcohol to 50mL deionized water, heating and stirring at 80°C for 3h, cooling at room temperature, and then mixing evenly with the dense composite material described in step S2, stirring for 30min, and finally adding propylene glycol, the amount of propylene glycol added is 0.5g, and an appropriate amount of propylene glycol is used as a plasticizer to make the material have better toughness and extend the service life. Magnetic stirring for 1h, standing for defoaming, and then cross-linking at 130°C for 15min, transferred to a plastic culture dish, dried to form a film at room temperature for 48h, and dried and stored after removing the film. The addition of polyvinyl alcohol further improves the heat resistance of the dense composite material and can also increase its transparency, so that it still has a certain aesthetics as a plastic substitute material. The material prepared by this process has good toughness, hydrophobicity and heat resistance, significantly extends the service life of the material, and obtains an environmentally friendly plastic substitute material based on cellulose.

[0041] In this example, the prepared dense composite material was subjected to scanning electron microscopy to observe its microscopic morphology. Figure 1 This is a SEM image of the dense composite material prepared in Example 1 magnified 2000 times, as shown in Figure 1 The dense composite material prepared in this embodiment presents a dense structure containing lamellae without residual voids.

[0042] Example 2

[0043] This embodiment proposes an environmentally friendly plastic substitute material based on cellulose, comprising the following components in parts by weight: 20 parts of nanofiller of molybdenum disulfide nanosheets composite transition metal carbide, 40 parts of lignin-containing nanocellulose suspension, 2 parts of citric acid, 3 parts of glycerol, and 10 parts of polyvinyl alcohol.

[0044] The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide comprises the following components in parts by weight: 30 parts of molybdenum disulfide nanosheet and 10 parts of transition metal carbide.

[0045] The lignin-containing nanocellulose suspension is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate and combining it with a high-pressure homogenization mechanical treatment.

[0046] The preparation method of the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps:

[0047] (1) 30 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid were dispersed in 25 mL of ultrapure water, ultrasonically treated for 5 h, and then centrifuged at 3000 rpm for 10 min. The supernatant was centrifuged at 7000 rpm for 10 min, and the product was collected. Thinner molybdenum disulfide sheets were separated from the bulk molybdenum dioxide by chemical stripping. The thinner sheets can be used as plasticizers for filler modification, improve the brittle fracture of cellulose materials, and have good mechanical properties. In addition, the sulfur atoms in the surface structure of molybdenum disulfide present certain protrusions, thereby achieving hydrophobic properties, which can reduce the occurrence of water absorption and moisture problems of cellulose materials, and obtain molybdenum disulfide nanosheets;

[0048] (2) Add 0.8 g of lithium fluoride to 20 mL of 30% hydrochloric acid solution, and then slowly add titanium aluminum carbide under gentle stirring. The amount of titanium aluminum carbide added is 0.8 g. Titanium aluminum carbide has a hexagonal layered structure. The aluminum atomic layer in titanium aluminum carbide can be etched by lithium fluoride and hydrochloric acid to prepare a new type of multilayer two-dimensional material. Then stir at 30°C for 12 hours, wash the resulting mixture with water until the pH is 6.0, then ultrasonicate for 0.5 hours, centrifuge at a speed of 2000 rpm, and centrifuge for 20 minutes. The precipitate is vacuum dried to obtain a transition metal carbide, which has a multilayer structure and a large surface area, improves the barrier properties, and reduces the entry of moisture. The nanometer size and good mechanical properties of this two-dimensional material can also enhance the strength and toughness of cellulose materials. The stable structure of the transition metal carbide can also enhance the heat resistance of cellulose materials, so that it can still maintain stable performance at high temperatures;

[0049] (3) The molybdenum disulfide nanosheets described in step (1) are dispersed in 5 mL of water and stirred for 10 minutes. The transition metal carbide described in step (2) is then added thereto. The mixture is ultrasonically treated for 15 minutes and then centrifuged. The precipitate is dried. The thinner and smaller molybdenum disulfide nanosheets are attached to the multiple layers of transition metal carbide to form a special layered structure, which effectively fills the gaps between the cellulose matrix and exhibits excellent mechanical properties, hydrophobic properties and heat resistance. The deformation and fracture of the cellulose material caused by moisture and heat can be reduced. The carrier effect of the transition metal carbide also reduces the accumulation and agglomeration of the molybdenum disulfide nanosheets, thereby obtaining a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides.

[0050] This embodiment provides a method for preparing an environmentally friendly plastic substitute material based on cellulose, which specifically comprises the following steps:

[0051] S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate were mixed at a molar ratio of 1:1, stirred in an oil bath at 70°C for 3h, cooled at room temperature, and then the obtained low eutectic solvent was heated to 110°C, followed by adding 9.0g wheat straw and stirring for 3h. After the reaction was completed, the wheat straw treated with the low eutectic solvent was filtered and washed with deionized water, and the filter residue was vacuum dried and dispersed in 50mL water, and mechanically treated with a high-pressure homogenizer. The treatment was cyclically treated 8 times at a pressure of 120MPa. More holes appeared on the surface of the wheat straw residue after the low eutectic solvent pretreatment, and the original smooth and complete structure was severely damaged. Hemicellulose and part of the lignin were removed. Combined with the high-pressure homogenization mechanical treatment, the obtained wheat straw residue was smaller in size and more thermally stable. The preparation method of lignin-containing nanocellulose using wheat straw as raw material can also be realized, wherein the remaining lignin can be used as a natural binder to enhance the bonding between components, further enhance the mechanical properties, and make it not easy to break, so as to obtain a lignin-containing nanocellulose suspension;

[0052] S2, disperse the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50mL deionized water, stir for 20min, then add citric acid, continue stirring for 20min, the amount of citric acid added is 0.2g, citric acid can form intermolecular covalent diester bonds with the hydroxyl groups of transition metal carbide and lignin-containing nanocellulose, so as to crosslink and stabilize the structure, improve the dispersion and bonding force between the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide and the matrix, prevent the nanosheet filler from falling off, and then mix with the lignin-containing nanocellulose suspension described in step S1, magnetic After vigorous stirring for 1 hour, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides are uniformly and stably dispersed on the structure containing lignin nanocellulose, effectively filling the gaps therein and forming a dense network structure, which can be used as a stress concentration point, can transmit and disperse external forces, enhance mechanical properties, reduce fractures, and can also highly isolate the entry of moisture and reduce the risk of moisture. Among them, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides contain C, O, N, and S elements. These doped elements can enhance the stability of the material crystal, thereby significantly improving the heat resistance and obtaining a dense composite material;

[0053] S3, adding polyvinyl alcohol to 50mL deionized water, heating and stirring at 70°C for 2h, cooling at room temperature, and then mixing evenly with the dense composite material described in step S2, stirring for 30min, and finally adding propylene glycol, the amount of propylene glycol added is 0.3g, and an appropriate amount of propylene glycol is used as a plasticizer to make the material have better toughness and extend the service life. Magnetic stirring for 1h, standing for defoaming, and then cross-linking at 120°C for 10min, transferring to a plastic culture dish, drying to form a film at room temperature for 48h, and drying and storing after removing the film. The addition of polyvinyl alcohol further improves the heat resistance of the dense composite material and can also increase its transparency, so that it still has a certain aesthetics as a plastic substitute material. The material prepared by this process has good toughness, hydrophobicity and heat resistance, significantly extends the service life of the material, and obtains an environmentally friendly plastic substitute material based on cellulose.

[0054] Example 3

[0055] This embodiment proposes an environmentally friendly plastic substitute material based on cellulose, comprising the following components in parts by weight: 25 parts of nanofiller of molybdenum disulfide nanosheets composite transition metal carbide, 45 parts of lignin-containing nanocellulose suspension, 3 parts of citric acid, 4 parts of glycerol, and 12.5 parts of polyvinyl alcohol.

[0056] The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide comprises the following components in parts by weight: 35 parts of molybdenum disulfide nanosheet and 15 parts of transition metal carbide.

[0057] The lignin-containing nanocellulose suspension is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate and combining it with a high-pressure homogenization mechanical treatment.

[0058] The preparation method of the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps:

[0059] (1) 35 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid were dispersed in 25 mL of ultrapure water, ultrasonically treated for 5.5 h, and then centrifuged at 3500 rpm for 10 min. The supernatant was centrifuged at 7500 rpm for 10 min, and the product was collected. Thinner molybdenum disulfide sheets were separated from the bulk molybdenum dioxide by chemical stripping. The thinner sheets can be used as plasticizers for filler modification, improve the brittle fracture of cellulose materials, and have good mechanical properties. In addition, the sulfur atoms in the surface structure of molybdenum disulfide present certain protrusions, thereby achieving hydrophobic properties, which can reduce the occurrence of water absorption and moisture problems of cellulose materials, and obtain molybdenum disulfide nanosheets;

[0060] (2) 0.9 g of lithium fluoride was added to 20 mL of a 30% hydrochloric acid solution, and then titanium aluminum carbide was slowly added under gentle stirring. The amount of titanium aluminum carbide added was 0.9 g. Titanium aluminum carbide has a hexagonal layered structure. The aluminum atomic layer in titanium aluminum carbide can be etched by lithium fluoride and hydrochloric acid to prepare a new type of multilayer two-dimensional material. The mixture was then stirred at 32.5°C for 18 hours. The resulting mixture was washed with water until the pH was 6.0, and then ultrasonicated for 0.75 hours, centrifuged at a speed of 2500 rpm and a centrifugal time of 25 minutes. The precipitate was vacuum dried to obtain a transition metal carbide, which has a multilayer structure and a large surface area, improves the barrier properties, and reduces the entry of moisture. The nanometer size and good mechanical properties of this two-dimensional material can also enhance the strength and toughness of cellulose materials. The stable structure of the transition metal carbide can also enhance the heat resistance of the cellulose material, so that it can still maintain stable performance at high temperatures;

[0061] (3) The molybdenum disulfide nanosheets described in step (1) are dispersed in 7.5 mL of water and stirred for 15 minutes. The transition metal carbide described in step (2) is then added thereto. The mixture is ultrasonically treated for 17.5 minutes and then centrifuged. The precipitate is dried. The thinner and smaller molybdenum disulfide nanosheets are attached to the multiple layers of transition metal carbide to form a special layered structure, which effectively fills the gaps between the cellulose matrix and exhibits excellent mechanical properties, hydrophobic properties and heat resistance. The deformation and fracture of the cellulose material caused by moisture and heat can be reduced. The carrier effect of the transition metal carbide also reduces the accumulation and agglomeration of the molybdenum disulfide nanosheets, thereby obtaining a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides.

[0062] This embodiment provides a method for preparing an environmentally friendly plastic substitute material based on cellulose, which specifically comprises the following steps:

[0063] S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate were mixed in a molar ratio of 1:1, stirred in an oil bath at 75°C for 3.5h, cooled at room temperature, and then the obtained low eutectic solvent was heated to 115°C, followed by adding 9.5g wheat straw and stirring for 3.5h. After the reaction was completed, the wheat straw treated with the low eutectic solvent was filtered and washed with deionized water, and the residue was vacuum dried and dispersed in 50mL water, and mechanically treated with a high-pressure homogenizer. The treatment was cyclically treated 9 times at a pressure of 125MPa. More holes appeared on the surface of the wheat straw residue after pretreatment with the low eutectic solvent, and the original smooth and complete structure was severely damaged. Hemicellulose and part of the lignin were removed. Combined with the high-pressure homogenization mechanical treatment, the obtained wheat straw residue was smaller in size and more thermally stable. The preparation method of lignin-containing nanocellulose using wheat straw as raw material can also be realized, wherein the remaining lignin can be used as a natural binder to enhance the bonding between components, further enhance the mechanical properties, and make it not easy to break, so as to obtain a lignin-containing nanocellulose suspension;

[0064] S2, disperse the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50mL deionized water, stir for 25min, then add citric acid, continue stirring for 25min, the amount of citric acid added is 0.3g, citric acid can form intermolecular covalent diester bonds with the hydroxyl groups of transition metal carbide and lignin-containing nanocellulose, so as to crosslink and stabilize the structure, improve the dispersion and bonding force between the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide and the matrix, prevent the nanosheet filler from falling off, and then mix with the lignin-containing nanocellulose suspension described in step S1, magnetic After stirring for 1.5 hours, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides are evenly and stably dispersed on the structure containing lignin nanocellulose, effectively filling the gaps therein and forming a dense network structure, which can serve as a stress concentration point, can transmit and disperse external forces, enhance mechanical properties, reduce fractures, and can also highly isolate the entry of moisture and reduce the risk of moisture. Among them, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides contain C, O, N, and S elements. These doped elements can enhance the stability of the material crystal, thereby significantly improving the heat resistance and obtaining a dense composite material;

[0065] S3, adding polyvinyl alcohol to 50mL deionized water, heating and stirring at 75°C for 2.5h, cooling at room temperature, and then mixing evenly with the dense composite material described in step S2, stirring for 30min, and finally adding propylene glycol, the amount of propylene glycol added is 0.4g, and an appropriate amount of propylene glycol is used as a plasticizer to make the material have better toughness and extend the service life. Magnetic stirring for 1h, standing for defoaming, and then cross-linking at 125°C for 12.5min, transferred to a plastic culture dish, dried to form a film at room temperature for 48h, and dried and stored after removing the film. The addition of polyvinyl alcohol further improves the heat resistance of the dense composite material and can also increase its transparency, so that it still has a certain aesthetics as a plastic substitute. The material prepared by this process has good toughness, hydrophobicity and heat resistance, significantly extends the service life of the material, and obtains an environmentally friendly plastic substitute based on cellulose.

[0066] Example 4

[0067] This embodiment proposes an environmentally friendly plastic substitute material based on cellulose, comprising the following components in parts by weight: 20 parts of nanofiller of molybdenum disulfide nanosheets composite transition metal carbide, 50 parts of lignin-containing nanocellulose suspension, 2 parts of citric acid, 5 parts of glycerol, and 10 parts of polyvinyl alcohol.

[0068] The nanofiller of molybdenum disulfide nanosheet composite transition metal carbide comprises the following components in parts by weight: 40 parts of molybdenum disulfide nanosheet and 10 parts of transition metal carbide.

[0069] The lignin-containing nanocellulose suspension is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate and combining it with a high-pressure homogenization mechanical treatment.

[0070] The preparation method of the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps:

[0071] (1) 40 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid were dispersed in 25 mL of ultrapure water, ultrasonically treated for 5 h, and then centrifuged at 4000 rpm for 10 min. The supernatant was centrifuged at 8000 rpm for 10 min, and the product was collected. Thinner molybdenum disulfide sheets were separated from the bulk molybdenum dioxide by chemical stripping. The thinner sheets can be used as plasticizers for filler modification, improve the brittle fracture of cellulose materials, and have good mechanical properties. In addition, the sulfur atoms in the surface structure of molybdenum disulfide present certain protrusions, thereby achieving hydrophobic properties, which can reduce the occurrence of water absorption and moisture problems of cellulose materials, and obtain molybdenum disulfide nanosheets;

[0072] (2) 1.0 g of lithium fluoride was added to 20 mL of a 30% hydrochloric acid solution, and then titanium aluminum carbide was slowly added under gentle stirring. The amount of titanium aluminum carbide added was 1.0 g. Titanium aluminum carbide has a hexagonal layered structure. The aluminum atomic layer in titanium aluminum carbide can be etched by lithium fluoride and hydrochloric acid to prepare a new type of multilayer two-dimensional material. The mixture was then stirred at 35°C for 12 hours. The resulting mixture was washed with water until the pH was 6.0, and then ultrasonicated for 0.5 hours, centrifuged at a speed of 3000 rpm and a centrifugal time of 20 minutes. The precipitate was vacuum dried to obtain a transition metal carbide, which has a multilayer structure and a large surface area, improves the barrier properties, and reduces the entry of moisture. The nanometer size and good mechanical properties of this two-dimensional material can also enhance the strength and toughness of cellulose materials. The stable structure of the transition metal carbide can also enhance the heat resistance of the cellulose material, so that it can still maintain stable performance at high temperatures;

[0073] (3) The molybdenum disulfide nanosheets described in step (1) are dispersed in 10 mL of water and stirred for 10 min. The transition metal carbide described in step (2) is then added thereto. The mixture is ultrasonically treated for 15 min and then centrifuged. The precipitate is dried. The thinner and smaller molybdenum disulfide nanosheets are attached to the multiple layers of transition metal carbide to form a special layered structure, which effectively fills the gaps between the cellulose matrix and exhibits excellent mechanical properties, hydrophobic properties and heat resistance. The deformation and fracture of the cellulose material caused by moisture and heat can be reduced. The carrier effect of the transition metal carbide also reduces the accumulation and agglomeration of the molybdenum disulfide nanosheets, thereby obtaining a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides.

[0074] This embodiment provides a method for preparing an environmentally friendly plastic substitute material based on cellulose, which specifically comprises the following steps:

[0075] S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate were mixed at a molar ratio of 1:1, stirred in an oil bath at 80°C for 3h, cooled at room temperature, and then the obtained low eutectic solvent was heated to 120°C, followed by adding 10.0g wheat straw and stirring for 3h. After the reaction was completed, the wheat straw treated with the low eutectic solvent was filtered and washed with deionized water, and the filter residue was vacuum dried and dispersed in 50mL water, and mechanically treated with a high-pressure homogenizer. The treatment was circulated for 10 times at a pressure of 130MPa. More holes appeared on the surface of the wheat straw residue after pretreatment with the low eutectic solvent, and the original smooth and complete structure was severely damaged. Hemicellulose and part of the lignin were removed. Combined with the high-pressure homogenization mechanical treatment, the obtained wheat straw residue was smaller in size and more thermally stable. The preparation method of lignin-containing nanocellulose using wheat straw as raw material can also be realized, wherein the remaining lignin can be used as a natural binder to enhance the bonding between components, further enhance the mechanical properties, and make it not easy to break, thereby obtaining a lignin-containing nanocellulose suspension;

[0076] S2, disperse the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50mL deionized water, stir for 20min, then add citric acid, continue stirring for 20min, the amount of citric acid added is 0.2g, citric acid can form intermolecular covalent diester bonds with the hydroxyl groups of transition metal carbide and lignin-containing nanocellulose, so as to crosslink and stabilize the structure, improve the dispersion and bonding force between the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide and the matrix, prevent the nanosheet filler from falling off, and then mix with the lignin-containing nanocellulose suspension described in step S1, magnetic After vigorous stirring for 1 hour, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides are uniformly and stably dispersed on the structure containing lignin nanocellulose, effectively filling the gaps therein and forming a dense network structure, which can be used as a stress concentration point, can transmit and disperse external forces, enhance mechanical properties, reduce fractures, and can also highly isolate the entry of moisture and reduce the risk of moisture. Among them, the nanofillers of molybdenum disulfide nanosheets composite transition metal carbides contain C, O, N, and S elements. These doped elements can enhance the stability of the material crystal, thereby significantly improving the heat resistance and obtaining a dense composite material;

[0077] S3, adding polyvinyl alcohol to 50mL deionized water, heating and stirring at 80°C for 2h, cooling at room temperature, and then mixing evenly with the dense composite material described in step S2, stirring for 30min, and finally adding propylene glycol, the amount of propylene glycol added is 0.5g, and an appropriate amount of propylene glycol is used as a plasticizer to make the material have better toughness and extend the service life. Magnetic stirring for 1h, standing for defoaming, and then cross-linking at 130°C for 10min, transferring to a plastic culture dish, drying to form a film at room temperature for 48h, and drying and storing after removing the film. The addition of polyvinyl alcohol further improves the heat resistance of the dense composite material and can also increase its transparency, so that it still has a certain aesthetics as a plastic substitute material. The material prepared by this process has good toughness, hydrophobicity and heat resistance, significantly extends the service life of the material, and obtains an environmentally friendly plastic substitute material based on cellulose.

[0078] Comparative Example 1

[0079] This comparative example provides an environmentally friendly plastic substitute material based on cellulose, which differs from Example 1 in that the nanofiller of molybdenum disulfide nanosheets composite transition metal carbide does not contain molybdenum disulfide nanosheets; the preparation method of the nanofiller of molybdenum disulfide nanosheets composite transition metal carbide does not include step (1); the preparation method of the environmentally friendly plastic substitute material based on cellulose is the same as that of Example 1.

[0080] Comparative Example 2

[0081] This comparative example provides an environmentally friendly plastic substitute material based on cellulose, which differs from Example 1 in that the nanofiller of molybdenum disulfide nanosheets composite transition metal carbides does not contain transition metal carbides; the preparation method of the nanofiller of molybdenum disulfide nanosheets composite transition metal carbides does not include step (2); the preparation method of the environmentally friendly plastic substitute material based on cellulose is the same as that of Example 1.

[0082] Comparative Example 3

[0083] This comparative example provides an environmentally friendly plastic substitute material based on cellulose, which differs from Example 1 in that the environmentally friendly plastic substitute material based on cellulose does not contain citric acid; the preparation method of the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide is the same as that in Example 1; and citric acid is not added in the preparation method S2 of the environmentally friendly plastic substitute material based on cellulose.

[0084] Experimental Example 1

[0085] Mechanical properties test

[0086] Test samples: cellulose-based environmentally friendly plastic substitute materials prepared in Examples 1-4 and Comparative Examples 1-3.

[0087] Test method: Cut the test samples into standard dumbbell-shaped small specimens, and use a universal testing machine to test the tensile strength and elongation at break according to the national standard GB13022-91. Set the tensile speed to 50mm / min, test 5 pieces in each group, and take the average value.

[0088] Figure 2 The mechanical properties of Examples 1-4 and Comparative Examples 1-3 are shown in the figure. As shown in the figure, the tensile strength and elongation at break of Examples 1-4 are 34.5-38.6 MPa and 55.2-59.7%, respectively, indicating that the mechanical properties are good; the tensile strength and elongation at break of Comparative Examples 1-3 are 26.0-28.5 MPa and 34.8-47.5%, respectively, indicating that the mechanical properties are poor; the nanofiller of the molybdenum disulfide nanosheet composite transition metal carbide of Comparative Example 1 does not contain molybdenum disulfide nanosheets, and the plasticizing effect of the molybdenum disulfide nanosheets cannot be exerted, which is not conducive to improving the toughness of the material, resulting in poor mechanical properties. Poor; the nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides in comparative example 2 does not contain transition metal carbides, which can neither improve the strength and toughness of the cellulose matrix by the two-dimensional material of the multi-layer sheets, nor reduce the stacking and agglomeration of the molybdenum disulfide nanosheets to limit their plasticizing effect, resulting in poor mechanical properties; the cellulose-based environmentally friendly plastic substitute material in comparative example 3 does not contain citric acid, which is not conducive to the compatibility and dispersibility of the nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides in the lignin-containing nanocellulose suspension, and cannot form a dense network structure, which is not conducive to enhancing toughness, resulting in poor mechanical properties.

[0089] Experimental Example 2

[0090] Hydrophobicity experiment

[0091] Test samples: cellulose-based environmentally friendly plastic substitute materials prepared in Examples 1-4 and Comparative Examples 1-3.

[0092] Test method: Use water vapor transmission rate tester (model W3 / 060) to test. Cut the test sample into a circle the size of a moisture permeable cup, place it in the moisture permeable cup with an appropriate amount of deionized water, seal the edge with a rubber ring, cover the moisture permeable cup and place it in the test chamber to start testing the water vapor transmission rate of the sample. Test 3 samples in each group and take the average value.

[0093] Figure 3 The water vapor transmission rate results of Examples 1-4 and Comparative Examples 1-3 are shown in FIG. As shown in the figure, the water vapor transmission rate of Example 1-4 is 2.186×10 -12 -2.305×10 -12 g cm / cm 2 s·Pa, indicating that the hydrophobicity is strong and it is not easy to absorb moisture; the water vapor transmission rate of comparative example 1-3 is 2.659×10 -12 -3.064×10 -12 g cm / cm 2 s·Pa, indicating that the hydrophobicity is weak and it is easy to absorb moisture; the nanofiller of molybdenum disulfide nanosheets composite transition metal carbide in comparative example 1 does not contain molybdenum disulfide nanosheets, which is not conducive to increasing the complexity of the layer structure and cannot extend the entry path of water molecules, resulting in weak hydrophobicity and easy moisture absorption; the nanofiller of molybdenum disulfide nanosheets composite transition metal carbide in comparative example 2 does not contain transition metal carbide, and cannot rely on the multilayer structure and large surface area of ​​transition metal carbide to improve the barrier performance, which increases the penetration and entry of water, resulting in weak hydrophobicity and easy moisture absorption; the cellulose-based environmentally friendly plastic alternative material in comparative example 3 does not contain citric acid, cannot form a dense network structure, is not conducive to highly isolating the entry of moisture, and cannot reduce the hydrophilicity of hydroxyl groups through cross-linking, resulting in weak hydrophobicity and easy moisture absorption.

[0094] Experimental Example 3

[0095] Heat resistance test

[0096] Test samples: cellulose-based environmentally friendly plastic substitute materials prepared in Examples 1-4 and Comparative Examples 1-3.

[0097] Test method: Cut the test sample into standard dumbbell-shaped small specimens, and conduct an accelerated test (90°C, 72h) according to the thermal oxidative aging test standard GB / T7141-2008. After the test, conduct an elongation at break test. Then, combine the data in Experimental Example 1 as the pre-test performance parameter, and calculate the decrease rate of elongation at break by the following formula. The greater the decrease rate of elongation at break, the worse the heat resistance.

[0098] Decrease rate of elongation at break (%) = (elongation at break before test - elongation at break after test) / elongation at break before test × 100%

[0099] Figure 4 The graph is a result of the decrease rate of the elongation at break of Examples 1-4 and Comparative Examples 1-3; as shown in the figure, the decrease rate of the elongation at break of Examples 1-4 is 1.8-3.8%, indicating that the heat resistance is better and it is not easy to deform at high temperature; the decrease rate of the elongation at break of Comparative Examples 1-3 is 8.5-13.4%, indicating that the heat resistance is poor and it is easy to deform at high temperature; the nanofiller of the molybdenum disulfide nanosheet composite transition metal carbide of Comparative Example 1 does not contain molybdenum disulfide nanosheets, which is not conducive to increasing the stability of the layer structure, and also lacks the stabilizing effect of the S element on the crystal, resulting in poor heat resistance and easy high temperature deformation; the molybdenum disulfide of Comparative Example 2 The nanofiller of the nanosheet composite transition metal carbide does not contain transition metal carbide, lacks the multi-layer stable structure of the transition metal carbide, and cannot reduce the accumulation of molybdenum disulfide nanosheets, resulting in poor heat resistance and easy high-temperature deformation; the cellulose-based environmentally friendly plastic alternative material of comparative example 3 does not contain citric acid, which is not conducive to enhancing the compatibility and dispersion stability of the nanofiller and matrix of the molybdenum disulfide nanosheet composite transition metal carbide, and cannot form a dense and stable network structure, thereby failing to fully fill the voids in the lignin-containing nanocellulose structure, resulting in poor heat resistance and easy high-temperature deformation.

[0100] The above experimental results show that the mechanical properties, hydrophobicity and heat resistance of Examples 1-4 of the present invention are significantly better than those of Comparative Examples 1-3. Among them, Example 1 using molybdenum disulfide nanosheets composite transition metal carbide nanofillers and citric acid has better tensile strength and elongation at break, stronger hydrophobicity and better heat resistance. The molybdenum disulfide nanosheets composite transition metal carbide nanofillers are dispersed in a lignin-containing nanocellulose suspension, and under the cross-linking action of citric acid, a dense composite material is formed, which fully fills the voids in the lignin-containing nanocellulose structure, forming a stable and dense network structure, which significantly enhances the toughness, hydrophobicity and heat resistance of the composite material, and reduces problems such as breakage and deformation caused by moisture or heat.

[0101] While the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that many changes, modifications, substitutions and alterations may be made to the embodiments without departing from the principles and spirit of the invention.

[0102] The present invention and its implementation methods are described above, which is not restrictive. The drawings are only one of the implementation methods of the present invention, and the actual application is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. An environmentally friendly plastic substitute material based on cellulose, characterized in that: The cellulose-based environmentally friendly plastic substitute material comprises the following components in parts by weight: 20-30 parts of nanofillers of molybdenum disulfide nanosheets composited with transition metal carbides, 40-50 parts of lignin-containing nanocellulose suspension, 2-4 parts of citric acid, 3-5 parts of propylene glycol, and 10-15 parts of polyvinyl alcohol; the nanofillers of molybdenum disulfide nanosheets composited with transition metal carbides comprise the following components in parts by weight: 30-40 parts of molybdenum disulfide nanosheets and 10-20 parts of transition metal carbides; the nanocellulose suspension containing lignin is prepared by pretreating wheat straw with a low eutectic solvent of benzyltrimethylammonium chloride and oxalic acid dihydrate, and combining it with high-pressure homogenization mechanical treatment.

2. A method for preparing an environmentally friendly cellulose-based plastic substitute material according to claim 1, characterized in that: The specific steps include: S1. Benzyltrimethylammonium chloride and oxalic acid dihydrate are mixed in a molar ratio of 1:1, stirred in an oil bath at 70-80°C for 3-4h, cooled at room temperature, and then the obtained low eutectic solvent is heated to 110-120°C, followed by adding 9.0-10.0g wheat straw, and stirring is continued for 3-4h. After the reaction is completed, the wheat straw treated with the low eutectic solvent is filtered and washed with deionized water, and the residue is vacuum dried and dispersed in 50mL water, and mechanically treated with a high-pressure homogenizer, and circulated for 8-10 times at a pressure of 120-130MPa to obtain a lignin-containing nanocellulose suspension; S2, dispersing the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide in 50 mL of deionized water, stirring for 20-30 min, then adding citric acid, continuing to stir for 20-30 min, and then mixing with the lignin-containing nanocellulose suspension described in step S1, and magnetically stirring for 1-2 h to obtain a dense composite material; S3. Add polyvinyl alcohol to 50 mL of deionized water, heat and stir at 70-80° C. for 2-3 h, cool at room temperature, mix evenly with the dense composite material described in step S2, stir for 30 min, finally add propylene glycol, stir magnetically for 1 h, let stand to defoam, then cross-link at 120-130° C. for 10-15 min, transfer to a plastic culture dish, dry to form a film at room temperature for 48 h, dry and store after removing the film, to obtain an environmentally friendly plastic substitute material based on cellulose.

3. The method for preparing an environmentally friendly cellulose-based plastic substitute material according to claim 2, characterized in that: In step S2, the amount of citric acid added is 0.2-0.4 g.

4. The method for preparing an environmentally friendly cellulose-based plastic substitute material according to claim 3, characterized in that: In step S3, the amount of glycerol added is 0.3-0.5 g.

5. The method for preparing an environmentally friendly cellulose-based plastic substitute material according to claim 4, characterized in that: The method for preparing the nanofiller of molybdenum disulfide nanosheet composite transition metal carbide specifically comprises the following steps: (1) Disperse 30-40 mg of molybdenum disulfide and 100 μL of polyacrylic acid liquid in 25 mL of ultrapure water, perform ultrasonic treatment for 5-6 h, centrifuge at 3000-4000 rpm for 10 min, take the supernatant and centrifuge at 7000-8000 rpm for 10 min, collect the product, and obtain molybdenum disulfide nanosheets; (2) adding 0.8-1.0 g of lithium fluoride to 20 mL of a 30% hydrochloric acid solution, then slowly adding titanium aluminum carbide under gentle stirring, and stirring at 30-35° C. for 12-24 h. The resulting mixture is washed with water until the pH is 6.0, and then ultrasonicated for 0.5-1 h, centrifuged at a speed of 2000-3000 rpm for 20-30 min, and the precipitate is vacuum dried to obtain a transition metal carbide; (3) Dispersing the molybdenum disulfide nanosheets described in step (1) in 5-10 mL of water, stirring for 10-20 min, adding the transition metal carbide described in step (2) thereto, ultrasonically treating for 15-20 min, and then centrifuging and drying the precipitate to obtain a nanofiller of molybdenum disulfide nanosheets composited with transition metal carbides.

6. The method for preparing an environmentally friendly cellulose-based plastic substitute material according to claim 5, characterized in that: In step (2), the amount of titanium aluminum carbide added is 0.8-1.0 g.

Citation Information

Patent Citations

  • Interface supramolecular reinforced nano composite material and preparation method thereof

    CN112375369A

  • Preparation method of nanocellulose / molybdenum disulfide piezoelectric composite film

    CN112646236A

  • Starch-based biodegradable plastic and preparation method thereof

    CN114381043A

  • MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel, epoxy resin-based composite material and preparation method of MXene-molybdenum disulfide-carbon nanofiber hybrid aerogel and epoxy resin-based composite material

    CN115785528A

  • Flexible packaging aerogel composite material and preparation method thereof

    CN116376267A